How do you solve #1/3t^2 + 3= 2t# using the formula?

Answer 1

First subtract #2t# from both sides to get:

#1/3t^2-2t+3 = 0#

Then using the quadratic formula:

#t = (2+-sqrt(2^2-(4xx1/3xx3)))/(2*1/3) = 3#

#1/3t^2-2t+3# is in the form #at^2+bt+c# with #a=1/3#, #b=-2# and #c=3#
So the roots of #1/3t^2-2t+3 = 0# are given by the quadratic formula:
#t = (-b+-sqrt(b^2-4ac))/(2a)#
#=(2+-sqrt(2^2-(4xx1/3xx3)))/(2*1/3)#
#=(2+-sqrt(4-4))/(2*1/3)#
#=cancel(2)/(cancel(2)*1/3)#
#=3#
Alternatively, multiply the quadratic equation by #3# to get:
#t^2-6t+9 = 0#

Notice that the coefficients (ignoring signs) are 1,6,9.

Does the pattern #1, 6, 9# ring any bells?
Well #169 = 13^2# and non-coincidentally:
#t^2-6t+9 = (t-3)^2#
#t^2-6t+9 = 0# when #(t-3) = 0#, that is when #t=3#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To solve the equation ( \frac{1}{3}t^2 + 3 = 2t ) using the formula, first rearrange the equation into standard quadratic form, ( at^2 + bt + c = 0 ). Then, apply the quadratic formula, which is given by:

[ t = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{{2a}} ]

where ( a ), ( b ), and ( c ) are the coefficients of the quadratic equation.

For the given equation ( \frac{1}{3}t^2 + 3 = 2t ), rearrange it into standard form:

[ \frac{1}{3}t^2 - 2t + 3 = 0 ]

Now, identify ( a = \frac{1}{3} ), ( b = -2 ), and ( c = 3 ).

Substitute these values into the quadratic formula:

[ t = \frac{{-(-2) \pm \sqrt{{(-2)^2 - 4(\frac{1}{3})(3)}}}}{{2(\frac{1}{3})}} ]

Simplify the expression:

[ t = \frac{{2 \pm \sqrt{{4 - 4}}}}{{\frac{2}{3}}} ] [ t = \frac{{2 \pm \sqrt{0}}}{{\frac{2}{3}}} ] [ t = \frac{2}{{\frac{2}{3}}} ]

Solve for ( t ):

[ t = 3 ]

Therefore, the solution to the equation ( \frac{1}{3}t^2 + 3 = 2t ) using the quadratic formula is ( t = 3 ).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7